The Mahānubhāvs - Rigopoulos, Antonio, 1962- (Cultural, historical and textual studies of religions., 2011)
"The ascetic devotional sect known as the Mahānubhāvs--'Those of the Great Experience'--arose in thirteenth-century Maharashtra and initially experienced a fairly rapid expansion across the northern and eastern areas of the region. However, by the end of the fourteenth century the sect had moved underground, having withdrawn to remote areas and villages in order to achieve defensive isolation from the larger Hindu context. Although the prominent leaders of the early Mahānubhāvs were Brahmans (often converts from the prevailing advaita vaisnavism), their followers were (and are) mostly non-Brahmans--those of the lower castes, and even untouchables. Thus the Mahānubhāvs were met with prejudice and distrust outside of their own closed circles, and this isolation continued until the beginning of the twentieth century. This volume offers an overview of the origins and main religious and doctrinal characteristics of the Mahānubhāv movement, with a particular focus on the aspects that reveal their difference and nonconformity."--Publisher's website.